Recent advances in hybrid sodium–air batteries. Issue 7 (10th April 2019) - Xu, Xiaolong; Hui, Kwan San; Dinh, Duc Anh; Hui, Kwun Nam; Wang, Hao
Abstract : Hybrid sodium–air battery (HSAB) principles are introduced, and the synthesis and rational designs of electrocatalysts based on the oxygen reduction reaction/oxygen evolution reaction are comprehensively reviewed for the purpose of providing insight into the development of efficient air electrodes. Furthermore, research directions of anodes, electrolytes, and air electrodes toward high-performance HSABs are proposed. Abstract : Among alkali–air batteries, aprotic sodium–air batteries (SABs) have attracted considerable attention owing to their high theoretical specific energy (1683 W h kg −1 ), high Na abundance, low-cost, and environment-friendliness. However, the application of SABs is currently restricted by their limited cycling life and low energy efficiencies due to insoluble and nonconductive discharge products (NaO2 and Na2 O2 ) generated on air electrodes. By contrast, hybrid SABs (HSABs) have resolved these daunting challenges by adopting an aqueous electrolyte cathode via a unique solid ceramic-ion-conductor-layer design separating the aprotic and aqueous electrolytes, resulting in extended cycle life. Thus, HSABs have aroused immense attention as promising next-generation energy storage systems. However, HSABs still face the key challenge of unsatisfactory cycling life that hinders their practical applications. In this review, HSAB principles are introduced, and the synthesis and rational designs of electrocatalysts based on the oxygen reduction reaction/oxygen evolution reaction from other metal–air batteries are comprehensively reviewed for the purpose of providing insight into the development of efficient air electrodes for HSABs. Furthermore, research directions of anodes, electrolytes, and air electrodes toward high-performance HSABs are proposed.